77 Clinical outcomes of treatment naive and nusinersen treated SMA1. (15th December 2021) - Weststrate, Harriet; manzur, Adnan; Stimpson, Georgia; Munot, Pinki; Main, Marion; Johnson, Emily; Abel, Francois; Chan, Elaine; Edel, Lisa; Smith, Natalie; Baranello, Giovanni; Muntoni, Francesco; et al.
Abstract : Background: Spinal Muscular Atrophy (SMA), a disorder caused by motor neuron degeneration, is characterized by muscle weakness, atrophy and hypotonia. Natural history studies of SMA Type 1 (SMA1) indicate that the majority would not survive beyond 2 years old. Nusinersen has dramatically altered the SMA phenotype with improved survival and motor outcomes. This study aims to describe care provided and outcomes of 'treatment-naive' SMA1 patients prior to nusinersen availability and of nusinersen treated SMA1 patients. Methods: This single centre retrospective audit identified 66 SMA1 patients assessed at GOSH between 2008–2021. Analysis considered SMA1 subtype, SMN2 copy number, motor abilities, nutritional support, respiratory support and survival. Results: We identified 38 patients in the treatment-naïve group and 28 patients in the nusinersen treated group. At time of analysis 37/38 patients had died in the treatment-naïve group, median age at death 0.66 years (range 0.17–3.17 years). In the nusinersen group 26/28 patients were still alive, median age at most recent follow up 4.88 years (range 1.33–11.3 years). In the treatment naïve group fifteen patients (41%) used non-invasive ventilation (NIV) and two (6%) used cough assist. 33 (92%) received enteral feeding: 2 (6%) gastrostomy fed (GT) and 31 (86%) nasogastric tube fed (NGT). In nusinersen treated group 26 (93%) used NIV and 25 (96%) used cough assist and 24 (86%) were enteral fed: 18 (64%) GT, 4 (14%) NGT and 2 (7%) NGT with some oral intake. Discussion: Survival in nusinersen treated SMA1 patients has significantly improved. A higher proportion of nusinersen treated SMA1 used NIV, cough assist and received a GT, likely reflecting their prolonged survival with older age at follow-up, cough assist introduction in 2015 and 2018 SMA standards of care compared to treatment-naïve. This study characterizes SMA1 patients cared for at GOSH and how our treatment practices have changed overtime.